EFEKTIFITAS PEMBERIAN WAKTU BEBAS BERMAIN UNTUK MENINGKATKAN MOOD POSITIVE SEBELUM KEGIATAN BELAJAR MENGAJAR BAGI SISWA SEKOLAH DASAR - Siti Pangestutik; Musyarofah H; Rahmawati R.A. (Universitas Katolik Soegijapranata, 2017)
This research’s goal to know the effectiveness of giving free time playing to improve positive mood of student. The subject in this research is student in third grade elementary school which amount 30 students. The design which is used is one group pretest posttest design experiment, with pretest and posttest which is done in three days continuously. Treatment that is given 30-minute playing time divided into two sessions, students are free to play by choosing the games provided and video playback on learning. The result of data analysis is obtained by using Paired Sample T-Test is t1 -0,722 with sign 0,476; T2 -0.403 with sign 0.690; T3 -0.626 with sign 0.536 (p> 0.05), it can be concluded that in this study there is no difference in positive mood before and after students given free play time treatment. This happens because the subjects involved in the research have been accustomed to being given free time playing. Therefore, free time playing is not effective to improve students' positive mood in this school. This is evidenced by the absence of significant positive mood score between before (pretest 1, 2 and 3) after posttest 1,2 and 3 giving free time treatment.